Research status of roof water and sand bursting disaster in thick bedrock stope of coal seam - Zhaoxing Liu; Shuning Dong; Xiaoming Guo; Xiaolong Li; Dongliang Chen (Scientific Reports)
Abstract The frequent occurrences of compound disasters involving roof water-sand inrush coupled with strong ground pressure manifestations in China’s western mining areas of Huanglong and Ningdong coal bases exhibit distinct characteristics from conventional non-dynamic water-sand inrush disasters in shallow-buried or near-unconsolidated stratum stopes. This study has identified two critical scientific challenges that constitute bottlenecks in revealing the disaster formation mechanism: the response patterns of abutment pressure distribution beneath hard rock strata and basic roof loading to the deterioration of weakly cemented formations; The dynamic formation mechanism of inrush from deteriorated weakly cemented strata and the evolutionary behavior of flow channels under hard rock fracturing. Three principal research components essential for elucidating the disaster mechanism have been systematically established: the feedback characteristics and response relationships of water-induced deterioration in weakly cemented strata to influencing factors; The variation patterns of stress conditions in overlying hard rock strata and basic roof with the deterioration of weakly cemented formations; The dynamic mechanisms of inrush from deteriorated weakly cemented strata and channel evolution under incremental loading. An integrated proactive prevention strategy has been proposed, featuring advanced hard rock pre-splitting and grouting modification of weakly cemented formations, which fundamentally alters the objective conditions for disaster initiation. These research outcomes will provide theoretical support for establishing a comprehensive prevention and control system against concurrent roof water-sand inrush and strong ground pressure manifestations, thereby ensuring the safe and large-scale exploitation of coal resources in western China’s coalfields.